Extensor mechanism ruptures of the knee: Differences in demographic data and long-term outcome after surgical treatment. Issue 10 (October 2015) - Negrin, Lukas L.; Nemecek, Elena; Hajdu, Stefan
Abstract Extensor mechanism ruptures are rare injuries. Until now, only few reports of medium or long-term outcomes have been published. Purpose The objective of this study was to quantify differences in demographic data and complications referring to patients with either quadriceps tendon ruptures (QTR) or patellar tendon (PTR) ruptures and to evaluate if complete functional restitution can be achieved after surgical treatment. Methods A search was conducted through the database of our level I trauma center in order to identify all patients surgically treated for QTRs or PTRs within 15 years and with a follow-up period of at least three years. Demographic data were collected by scanning their medical records. Of all patients available for a final check-up, their outcomes were assessed using the Knee Society Clinical Rating System (KSS), the Oxford Knee Score (OKS) and the Reduced WOMAC Function Scale (rWOMAC). Furthermore, patient perception (PP) was evaluated. Results 130 patients (93 QTRs and 43 PTRs) met the inclusion criteria. 8% of the QTR- and 13% of the PTR-patients suffered wound healing disorders/septic complications. 8% in the QTR-group sustained a rerupture. 62% of all patients were available for clinical evaluation, the mean follow-up period was 10.3 years in the QTR-group and 9.0 years in the PTR-group. In both groups good to excellent outcomes were revealed. Of the KSS-Knee, the mean score value was 93.1 in the QTR-group and 91.4 in the PTR-group; KSS-Function: 89.7/96.4; OKS: 14.6/13.1; rWOMAC: 95.7/98.3; PP: 88.5/93.3. QTR-patients suffering a rerupture had a significantly worse outcome in all scores except for the KSS-Knee (p ≤ 0.026), whereas PTR-patients with healing disorders/septic complications showed a significant inferior outcome solely in the PP-scale (p = 0.02).